A Study on Consumer Preference towards the Improvements in Online Shopping Overpackaging - Corrinne Mei Jyin Lee; Chee Cheng Chong (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2023)
Online shopping and delivery services are becoming increasingly popular. The purchase experience of consumers, as well as business processes, have been significantly changed by this phenomenon. Yet, overpackaging issues have caused a major environmental concern when consumers dispose of the packaging after unboxing parcels. A survey of 200 respondents aged above 18 with experience in online shopping was conducted. The study model was developed based on the value co-creation (VCC) theory to investigate consumer preferences towards improvements in online shopping overpackaging. The findings show that implementing packaging material (PM), and environmental concern (EC) have a beneficial impact on consumer preferences. Based on the findings, this paper recommends that online merchants need to be concerned about the packaging material, in view that consumers show their environmental concern to protect the environment. In addition, the government can provide a better recycling system for consumers in relation to the disposal of packaging.